Effect of particle size, extraction time and flow rate on the supercritical carbon dioxide extraction of oil yield from citrus microcarpa pericarp - Norlisa, Mili; Zuhaili, Idham; Noor Azwani, Mohd Rasidek (AIP Publishing, 2024)
The purpose of this research is to determine the effect of particle size, extraction time and flow rate on the supercritical carbon dioxide extraction of oil yield from Citrus Microcarpa Pericarp using the supercritical carbon dioxide (SC-CO2) method. The SC-CO2 extraction was conducted at constant pressure and temperature, 30MPa and 40°C. The result indicates that 240 minutes was the optimal extraction duration for determining the flow rate. The trend and findings for extraction yield differed across all investigated factors. Results suggest that a low flow rate, 3 ml/min, 240 minutes of extraction time and specific particle size of 500-600 µm could increase the oil yield. Hence, SC-CO2 extraction parameters can be adjusted to increase oil extraction from the overall extract.